2003
DOI: 10.1159/000072067
|View full text |Cite
|
Sign up to set email alerts
|

Topical Vaccination of DNA Antigens: Topical Delivery of DNA Antigens

Abstract: Topical DNA vaccines have been shown to elicit both broad humoral and cellular immune responses in vivo. The skin is an attractive site for the delivery of DNA antigens for DNA vaccination. However, due to skin’s barrier properties, the penetration of DNA and the applications of topical vaccination are limited. To improve permeability, chemical and physical approaches have been examined to decrease stratum corneum barrier properties. Topical vaccination has been achieved using topical application of naked DNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 53 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…In contrast, topical application of this vaccine with stripping induced strong antibody responses and elicited substantial CTL responses. There was a significant difference between the results of topical application with and without stripping [27,52].…”
Section: Tape Stripping and Topical Vaccinationmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, topical application of this vaccine with stripping induced strong antibody responses and elicited substantial CTL responses. There was a significant difference between the results of topical application with and without stripping [27,52].…”
Section: Tape Stripping and Topical Vaccinationmentioning
confidence: 84%
“…Skin accessibility makes it an easy target for vaccination. Thus, skin is an attractive target site for topical vaccination and has become the focus of intense study for the induction of antigen-specific immune responses [51,52]. Wang et al [53] observed that protein penetrates the SC barrier following occlusion by patch application, but im-Choi/Zhai/Löffler/Dreher/Maibach Cervical lymph node cells (effectors) obtained from mice immunized 10 days earlier with tyrosinase-related protein 2 peptide (VYDFFVWL, 96 Ìg/mouse) either through intact earlobes or earlobes tape stripped 12 h earlier were subjected to CTL assay using L kb target cells pulsed with tyrosinase peptide.…”
Section: Tape Stripping and Topical Vaccinationmentioning
confidence: 99%
“…This barrier disruption process is painless, highly effective in augmenting the transfer of macromolecules such as proteins or DNA into skin, and has been successfully utilized in human clinical trials. 46,[48][49][50] An additional advantage is that physical barrier disruption itself has been shown to trigger activation of keratinocytes and LCs in skin, providing some level of 'built-in' adjuvant response. [44][45][46][49][50][51][52] We thus tested a model where the dorsal ears of anesthetized mice were tape-stripped followed by application of as-assembled, airdried (Poly-1/ova) 40 films on either glass or PDMS substrates, fixed in place by surgical tape against the exposed ear skin, mimicking a common strategy used in skin vaccination studies 45,46 (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…In an in vivo mouse model, the application of pEGFP-N1 DNA led to the generation of GFP-specific antibodies. The topical spray application of pEGFP-N1 liposomal DNA formulations is a suitable method for plasmid DNA delivery to the skin, yielding significant gene expression [98,99]. Skin is an active immune surveillance site and shows both specific (immunity) and non-specific (inflammation) response for topical DNA vaccine [100].…”
Section: Topical Route For Dna Immunizationmentioning
confidence: 99%